As representações sociais sobre a figura paterna : um estudo com crianças e adolescentes em situação de risco e de vulnerabilidade social - Silva, Maria Sandra Montenegro (2008)
This research aimed to investigate the social representations on the paterne figure in the speech some children and adolescents at risk and social vulnerability. In search of actors are part of a public school, have father, mother and brothers, but they are part of a segment where the conditions of life its very difficult. What drove us to investigate the paternal figure was the ideas in the books and in the media which the father is trying to participate more the lives of the children. Our research indicates this is a behavior still in process and does not extend to all families. The research was qualitative-interpretative stamp, introduced in the social representations of children and adolescents and idealized father, but not impossible to be exercised by improving the quality of their relationships with their children and the family in general. The findings which partial, show a marked vulnerability to affective ties, they also managed to identify attacks silent, subtle, disguised in various feelings between parents and children